Plato's Cratylus - Sedley, David (Cambridge University, 2013)
This book presents a global reinterpretation of Cratylus, Plato's only dialogue devoted to the subject of language. It is designed to be accessible to anyone interested either in Plato or in the history of linguistic thought. The main text does not presuppose prior expertise in Plato or knowledge of Greek.